2018
DOI: 10.5114/aic.2018.74358
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA levels differ with respect to carotid plaque characteristics and symptom occurrence in patients with carotid artery stenosis and provide information on future cardiovascular events

Abstract: IntroductionCirculating microRNAs (miRNAs) levels are potentially important biomarkers and therapeutic targets of cerebral ischemic event (CIE) in patients with internal carotid artery stenosis (ICAS).AimThis prospective study investigated associations between circulating miRNAs and symptomatic and asymptomatic ICAS, carotid plaque morphology and future cardiovascular events.Material and methodsCirculating miRNAs (miR-1-3p, miR-16-5p, miR-34a-5p, miR-124-3p, miR-133a-3p, miR-133b, miR-134-5p, miR-208b-3p, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…It was reported that a wide variety of pro‐inflammatory and anti‐inflammatory miRNAs could play distinct roles in the pathogenesis of IS in relevance to neuro‐inflammation (Gaudet, Fonken, Watkins, Nelson, & Popovich, ), as well as in the pathobiology of atherosclerosis (Feinberg & Moore, ; Laffont & Rayner, ). Consequently, similar to the conventional inflammatory biomarkers, miRNAs were also identified as potential diagnostic or prognostic targets for IS (Badacz et al, ; Gacon et al, ; Li, Efendizade, & Ding, ; Shekhar et al, ; Xu et al, ). A recent study further demonstrated that circulating miRNAs in human blood serum might be used to differentiate the IS etiological subtypes (Gui et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a wide variety of pro‐inflammatory and anti‐inflammatory miRNAs could play distinct roles in the pathogenesis of IS in relevance to neuro‐inflammation (Gaudet, Fonken, Watkins, Nelson, & Popovich, ), as well as in the pathobiology of atherosclerosis (Feinberg & Moore, ; Laffont & Rayner, ). Consequently, similar to the conventional inflammatory biomarkers, miRNAs were also identified as potential diagnostic or prognostic targets for IS (Badacz et al, ; Gacon et al, ; Li, Efendizade, & Ding, ; Shekhar et al, ; Xu et al, ). A recent study further demonstrated that circulating miRNAs in human blood serum might be used to differentiate the IS etiological subtypes (Gui et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with symptoms from the carotid artery were characterized with lower expression of miR-1. This finding might be potentially attributed to the different mechanisms of coronary and carotid ischemia [22][23][24].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Dolz et al tried to construct specific circulating miRNA expression profiles in asymptomatic CAS patients by using Affymetrix microarrays, and several miRNAs were determined to be aberrantly expressed by using qRT-PCR, including miR-199b-3p, miR-27b-3p, miR-130a-3p, miR-221-3p, and miR-24-3p [ 9 ]. Another study by Badacz et al reported that several miRNAs were differentially expressed in symptomatic CAS patients compared with asymptomatic cases, the dysregulation of miRNAs showed a close association with plaque morphology and structure and might be potential prognostic factors for future cardiovascular events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%